Nanoparticle-imprinted polymers: shell-selective recognition of Au nanoparticles by imprinting using the Langmuir-Blodgett method. - Bruchiel-Spanier, Netta; Mandler, Daniel. (ChemElectroChemChemElectroChem, 2015)
Speciation of nanoparticles, i.e., their differentiation based on size, shape and stabilizing shell is becoming important since their properties depend on these parameters. Nanoparticle-imprinted polymers (NIPs) are a new approach that aims to selectively recognize nanoparticles based on their structural properties. In this study, monolayers of cellulose acetate (CA) accommodating gold nanoparticles stabilized with dodecanethiol (AuNPs/C12) are transferred onto indium tin oxide (ITO) by the Langmuir-Blodgett technique. One to five monolayers are assembled. Electrochem. oxidn. dissolves the AuNPs/C12 to form cavities in the films, which fit the size and shape of the AuNPs/C12. Reuptake of the nanoparticles from a soln. is successful using the imprinted films, whereas the control films contg. only CA layers do not reuptake the AuNPs/C12. The NIPs are highly selective and other gold nanoparticles stabilized by other thiols are not recognized by the imprinted matrix. [on SciFinder(R)]
CAPLUS AN 2015:922879(Journal; Online Computer File)
Keywords: gold nanoparticle selective recognition imprinting cellulose acetate film dodecanethiol